Fluorescence lifetime microscopy of NADH distinguishes alterations in cerebral metabolism in vivo - Yaseen, Mohammad A; Sutin, Jason; Wu, Weicheng; Fu, Buyin; Uhlirova, Hana; Devor, Anna; Boas, David A; Sakadžić, Sava (Biomedical optics express, 2017)
Evaluating cerebral energy metabolism at microscopic resolution is important for comprehensively understanding healthy brain function and its pathological alterations. Here, we resolve specific alterations in cerebral metabolism in vivo in Sprague Dawley rats utilizing minimally-invasive 2-photon fluorescence lifetime imaging (2P-FLIM) measurements of reduced nicotinamide adenine dinucleotide (NADH) fluorescence. Time-resolved fluorescence lifetime measurements enable distinction of different components contributing to NADH autofluorescence. Ostensibly, these components indicate different enzyme-bound formulations of NADH. We observed distinct variations in the relative proportions of these components before and after pharmacological-induced impairments to several reactions involved in glycolytic and oxidative metabolism. Classification models were developed with the experimental data and used to predict the metabolic impairments induced during separate experiments involving bicuculline-induced seizures. The models consistently predicted that prolonged focal seizure activity results in impaired activity in the electron transport chain, likely the consequence of inadequate oxygen supply. 2P-FLIM observations of cerebral NADH will help advance our understanding of cerebral energetics at a microscopic scale. Such knowledge will aid in our evaluation of healthy and diseased cerebral physiology and guide diagnostic and therapeutic strategies that target cerebral energetics.
Keywords: (180.4315) Nonlinear microscopy; (170.0170) Medical optics and biotechnology; (170.3650) Lifetime-based sensing